Meningkatkan Hasil Belajar IPS Menggunakan Model Pembelajaran Kooperatif Tipe Examples Non Examples Pada Siswa Kelas IV-B SDN 4 Danger - Made Ayu Pransisca; Munawir Gazali; Harun Arrasyid (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
The purpose of this study was to improve social studies learning outcomes in the materials of production technology, transportation and communication from time to time by applying the Examples Non Examples cooperative learning model to students in class IV-B at SDN 4 Danger. The type of research used is Classroom Action Research (PTK) which will be conducted at SDN 4 Danger in the first semester of the 2022/2023 school year. The research subjects were students of grade IV-B SDN 4 Danger, totaling 31 students, with 22 male students and 9 female students. This research was conducted in 2 cycles, each cycle consisting of 2 meetings. The procedure for each cycle consists of planning, action, observation, and reflection. The data obtained in this study included observation sheets of student activities, observation sheets of teacher activities, assessment of cognitive aspects (learning achievement tests), affective aspects (responsibility, curiosity, and cooperation), and psychomotor aspects (group presentations). The results showed that by applying the Examples Non Examples type of cooperative learning model it could improve social studies learning outcomes in production technology, transportation and communication from time to time students of class IV-B SDN 4 Danger. This can be seen from the results obtained in each cycle, in the first cycle the cognitive aspects of student learning outcomes were 74% in the second cycle increased to 87%. In the first cycle, the affective aspect of student learning outcomes was 74%, in the second cycle it increased to 93%. Then in the first cycle the completeness of student learning outcomes in the psychomotor aspects of 77% in the second cycle increased to 100%. So it can be said that the research has been successful and in accordance with the indicators of success